Clinical efficacy of fecal microbiota transplantation in alleviating depressive symptoms: a meta-analysis of randomized trials - Zhang, Xiaotao; Li, Ying; Guo, Yueyue; Sun, Jia; Yang, Yang (Frontiers in Psychiatry, 2025)
BackgroundDepressive symptoms are common in neuropsychiatric disorders, significantly affecting quality of life and posing challenges to treatment. While pharmacological and psychological therapies remain standard, many patients show limited response. Fecal microbiota transplantation (FMT), which aims to restore gut microbial balance, has emerged as a novel approach for alleviating depressive symptoms by modulating the gut-brain axis. This study aims to conduct a comprehensive synthesis and quantitative evaluation of current evidence to elucidate the therapeutic potential of FMT in the management of depressive symptomatology.MethodsFollowing PRISMA guidelines, we conducted a systematic search across PubMed, Embase, Web of Science, the Cochrane Library, and CINAHL from January 1, 2000, to December 31, 2024. 12 randomized controlled trials (RCTs) with 681 participants were included. The standardized mean difference (SMD) was calculated to evaluate FMT’s effect on depressive symptoms. Subgroup analyses examined effects by delivery routes, follow-up duration, and clinical population.ResultsFMT significantly reduced depressive symptoms (SMD = -1.21; 95% CI: -1.87 to -0.55; p = 0.0003). Sensitivity analysis confirmed statistical significance (SMD = -0.56; 95% CI: -0.86 to -0.26; p = 0.001). Both oral capsule and direct gastrointestinal administration were effective, with greater effects seen in direct gastrointestinal delivery (SMD = -1.06 vs. -1.29). Improvements were most notable in the short- to mid-term; effects diminished by 6 months. Subgroup analysis showed stronger effects in patients with irritable bowel syndrome (IBS) (SMD = -1.06) than in those with neurological/psychiatric-related conditions (SMD = -0.67), with moderate heterogeneity (I² = 47%).ConclusionsThis meta-analysis supports FMT as an effective adjunctive therapy for depressive symptoms, especially in individuals with IBS. Endoscopic or enema routes appear more efficacious than oral capsules. While short- and mid-term benefits are evident, sustained effects require further investigation through long-term, high-quality RCTs.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42025638185.